LIFE SKILLS BERWIRAUSAHA MAHASISWA TATA BUSANA JURUSAN ILMU KESEJAHTERAAN KELUARGA FPP UNP - Amelia, Desry; Nazar, Ernawati; Nelmira, Weni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
Life skills is a skill that is needed to work in addition to academic skills. oriented life skills to equip students in improving their standard of living as well looking at their capabilities so as to overcome the problems faced and take advantage of opportunities and clever mingle in society. But still many students who do not have skills entrepreneurship. The synergy of life skills in entrepreneurship is needed in term of personal skills, social skills, academic skills, and vocational skills. Research of design is quatitative descriptive aims to describe the life skills of entrepreneurship fashion students.Keywords : Life skills, Entrepreneurship